Deposition of syngas tar in fuel supplying duct of a biomass gasifier: A numerical study. (1st August 2020) - Casari, Nicola; Pinelli, Michele; Suman, Alessio; Candido, Antonio; Morini, Mirko
Abstract: Biomass gasification is increasingly regarded as a promising clean energy source. Nonetheless, the gasification technology still has some open issues that lower the plant availability, efficiency and the full applicability of the process. Among the others, tar condensation and deposition during the process represents a real hazard, resulting in the clogging of fuel lines, filters, and engine. Therefore, from the operator standpoint, it is very important to be able to predict the location where tar will deposit along the piping and its deposition rate, in order to schedule the cleaning and to focus on specific section to reduce the down-time of the system. In this work, Computational Fluid Dynamic is employed to help in the prediction of the rate and area of deposit growth. Besides, the effect of the insulation is investigated, showing the importance of an adequate coating with non-conductive material on the amount of tar condensed. The tar deposition law implemented relies on a compound-dependent condensation temperature.